Determinants and prospect of bilateral trade flow of Malaysia and its African OIC member countries - Agboola, Yusuf Hammed (2018)
International trade has always been playing a crucial role in the process of growth and development in Malaysia. This study examined the determinants and prospect of bilateral trade flow of Malaysia and Africa OIC member countries from the period 1985 to 2015.It is aimed to examine their trends, pattern of trade, determinants of exports and imports, and assess their future prospects. Quantitative method of analysis was used to achieve the objectives of this study. The methods employed were dynamic panel data using Gravity Model (GM) of trade, Poisson Pseudo Maximum likelihood (PPML), and Dynamic Ordinary Least Square (DOLS), to test for the long run relationship. Findings from the gravity results showed that exports and imports flow from Malaysia to OIC countries in Africa were determined by bilateral distance, Gross Domestic Product (GDP) per capita, GDP similarities, common colony, population growth and exchange rate. However, weak institutional quality among the OIC countries in Africa have been hindering bilateral trade flows between Malaysia and OIC countries in Africa. On these premises, the study suggested that OIC countries in Africa must address their weak institutional structures within their region in order to enhance bilateral trade between Malaysia and OIC countries in Africa. Findings from the analyseswere constructed by employing the SWOT analysis to investigate future prospects of bilateral trade relationship between Malaysia and OIC member countries in Africa. Based on these findings, some policy issues were highlighted, and policy recommendations were developed, such as accelerating the effort to improve the environments of Islamic finance and banking, establishing the Islamic Common Market (ICM) and further liberalising the economy through tariff reduction.